2022
DOI: 10.7717/peerj.14207
|View full text |Cite
|
Sign up to set email alerts
|

Regional water footprint assessment for a semi-arid basin in India

Abstract: Water footprint assessment enables us to pinpoint the impacts and limitations of the current systems. Identifying vulnerabilities across various regions and times helps us prepare for suitable actions for improving water productivity and promoting sustainable water use. This study aims to provide a comprehensive evaluation of the sector-wise water footprint in the Banas River Basin from 2008–2020. The water footprint of the Banas River Basin was estimated as 20.2 billion cubic meters (BCM)/year from all sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In order to account for spatial variations and minimize the number of required simulations, the basin was divided into homogeneous land units (LU) based on factors such as land use, soil, and agro-climatological characteristics [ 27 ]. To achieve this, different thematic layers, including soil, AESR, LULC, basin boundaries, and district boundaries, were overlaid, and LU polygons were generated for each district using the intersect feature in ArcGIS [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to account for spatial variations and minimize the number of required simulations, the basin was divided into homogeneous land units (LU) based on factors such as land use, soil, and agro-climatological characteristics [ 27 ]. To achieve this, different thematic layers, including soil, AESR, LULC, basin boundaries, and district boundaries, were overlaid, and LU polygons were generated for each district using the intersect feature in ArcGIS [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was opined that in order to have a comprehensive understanding of virtual water trade, non-water factors of production need to be taken into consideration". Mehla [37] conducted study to estimate water footprint of major crops of Banas river basin and found out that the water footprint doubled in last decade for major crops of basin such as wheat, bajra, maize, rapeseed and mustard.…”
Section: Water Footprint Studies In Indiamentioning
confidence: 99%
“…However, there are precedents of successful modeling with shorter periods ranging from 6 to 15 years ( Marcinkowski & Mirosław-Świątek, 2020 ; Wielgat et al, 2021 ; Goshime et al, 2021 ; Mehla, 2022 ). Moreover, literature suggests modeling periods varying from 15 to 20 years ( Khoshkhoo et al, 2015 ; Rasoulzadeh Gharibdousti, Kharel & Stoecker, 2019 ; Dehghanipour et al, 2019 ; Lerat et al, 2020 ; Bazzi, Ebrahimi & Aminnejad, 2021 ; Nazeer et al, 2022 ), highlighting the preference for extended modeling periods ( Schuol et al, 2008 ; Li et al, 2015 ; Adla, Tripathi & Disse, 2019 ; García-Romero et al, 2019 ; Lakshmi & Sudheer, 2021 ) that include validation and warm-up spans as well as modeling for complete or discontinuous periods ( Zhang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%